THE STRUCTION OF SYNONYMS IN UZBEK AND ENGLISH LANGUAGES - Karimova Gulshod Mamatkadirovna; Sirayeva S. A. (Journals Park Publishing, 2023)
Synonyms are also widely used in the Uzbek language. A group of words that are synonymous with each other is called a line of synonyms. One word in a line of synonyms is the head word (main word). The main word becomes popular and important compared to its fellows.
Keywords: Uzbek language, linguistics, synonym, word groups, synonyms, phrase.